Euclid, Elements, Book II. Translated into Polish from the text of Heiberg - Błaszczyk, Piotr; Mrówka, Kazimierz (Annales Universitatis Paedagogicae Cracoviensis | Studia ad Didacticam Mathematicae Pertinentia, 2020)
Tłumaczenie